Engineering education research and development in curriculum and instruction - Heywood, John (Wiley-Interscience, 2005)
A synthesis of nearly 2,000 articles to help make engineers better educators While a significant body of knowledge has evolved in the field of engineering education over the years, much of the published information has been restricted to scholarly journals and has not found a broad audience. This publication rectifies that situation by reviewing the findings of nearly 2,000 scholarly articles to help engineers become better educators, devise more effective curricula, and be more effective leaders and advocates in curriculum and research development. The author's first objective is to provide an illustrative review of research and development in engineering education since 1960. His second objective is, with the examples given, to encourage the practice of classroom assessment and research, and his third objective is to promote the idea of curriculum leadership.